2003
DOI: 10.1016/s0002-9440(10)63861-8
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Dehydrogenase-2 Is Inhibited by Compounds that Induce Congenital Diaphragmatic Hernias in Rodents

Abstract: Currently, the etiology of the serious developmental anomaly congenital diaphragmatic hernia (CDH) is unknown. We have used an animal model of CDH to address this issue. We characterized four separate teratogens that produced diaphragmatic defects in embryonic rats that are similar to those in infants with CDH. We then tested the hypothesis that all these agents share the common mechanism of perturbing the retinoid-signaling pathway. Specifically, inhibition of retinal dehydrogenase-2 (RALDH2), a key enzyme ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
128
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 44 publications
2
128
0
Order By: Relevance
“…Indeed, one clinical study demonstrated the presence of decreased levels of retinol and retinol-binding protein in human CDH, suggesting a possible deterioration of retinol transport across the placenta (46). Regarding the nitrofen-induced CDH model, it was already demonstrated that nitrofen inhibits retinal dehydrogenase 2 (RALDH2), a key enzyme responsible for the conversion of retinal to retinoic acid (47). Moreover, the co-administration of retinoids (Vitamin A or retinoic acid) in nitrofeninduced CDH induces lung growth and reduces the incidence of CDH (9,10,48).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one clinical study demonstrated the presence of decreased levels of retinol and retinol-binding protein in human CDH, suggesting a possible deterioration of retinol transport across the placenta (46). Regarding the nitrofen-induced CDH model, it was already demonstrated that nitrofen inhibits retinal dehydrogenase 2 (RALDH2), a key enzyme responsible for the conversion of retinal to retinoic acid (47). Moreover, the co-administration of retinoids (Vitamin A or retinoic acid) in nitrofeninduced CDH induces lung growth and reduces the incidence of CDH (9,10,48).…”
Section: Discussionmentioning
confidence: 99%
“…The data derived from the study clearly demonstrated that all four CDH-inducing compounds inhibit RALDH-2 in a dose-dependent manner. Further, the most potent inhibitor of RALDH-2, bisdiamine, was also the most effective at inducing diaphragmatic defects in embryonic rats (13).…”
Section: Retinoid Signaling and Cdhmentioning
confidence: 91%
“…The similarities hold true with regard to the specific location and extent of diaphragmatic defects as well as the periodic occurrence of associated anomalies affecting cardiac, pulmonary and skeletal tissues. More recently, three additional compounds that cause diaphragmatic defects in rats have been characterized (13). Biphenyl carboxylic acid (BPCA), bisdiamine [N,N'-octamethylenebis (dichloroacetamide)] and SB-210661, all induce diaphragmatic as well as cardiopulmonary, dermal and skeletal defects in the fetuses isolated from treated pregnant rats.…”
Section: Insights Into the Pathogenesis Of Cdh From Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormalities in the vitamin A status and/or metabolism may also play a role in the genesis of congenital diaphragmatic hernia (CDH). CDH can be induced in rodent by either maternal retinol deficiency during pregnancy (Anderson, 1941 and1949;Warkany and Wilson, 1948;Wilson et al, 1953;Mendelsohn et al, 1994;Lohnes et al, 1995), or administration of nitrofen, a retinal dehydrogenase type 2 (RalDH2) inhibitor reducing the RA production (Nakao and Ueki, 1987;Kluth et al, 1990;Mey et al, 2003). Therefore maternal administration of retinol or RA was recently proposed as a potential therapeutic measure to decrease foetal lung abnormalities in the rodent 'nitrofen-toxic' CDH (Thebaud et al, 1999;Babiuk et al, 2004;Oshiro et al, 2005).…”
mentioning
confidence: 99%